Asymetria dostosowania stóp procentowych na polskim rynku depozytów międzybankowych - Miłobędzki, Paweł; Blangiewicz, Maria (Asymmetry in the adjustment of the WIBOR interest rates at the Polish interbank market, 2006)
The paper is devoted to the analysis of the interest rates spreads at the Polish Interbank market. It assumed that in the long run WIBOR long and short interest rates are in equilibrium, in the short run however, the adjustment towards equilibrium is asymmetric due to different behaviour of traders in bull and bear markets. The analysis is nested in the bivariate vector error correction model (BVEC) framework with the error correcting term build upon threshold (TAR) and momentum threshold autoregressions (M-TAR). The inference about the nature of the interest rates spreads is based upon the daily time series from the period January 4, 1999-April 1, 2005. The main finding is that in the long run the long-short rate relations are constant and linear atractors. Akaike and Schwarz-Bayes system criteria strongly support the hypothesis stating that the proper model for the long-short interest rates relations are the bivariate VECs with either TAR or M-TAR correcting term in which the shorter rate is the Granger cause for the longer rate, and the longer rate is the cause for the shorter rate. The RPP’s attitude towards the monetary policy is found to have an impact on interest rates behaviour.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 338-350